2020
DOI: 10.3390/su12052059
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Drivers of National-Level Energy Audit Behavior: Demographics and Socioeconomic Characteristics

Abstract: The energy audit-an assessment of a home's energy systems performed by a trained auditor in order to provide the resident with strategies for saving energy and money-is provided by many utility companies throughout the United States for free or at a reduced cost. The uptake of such programs is generally low, and little is known about audit participants. Importantly, as more evidence points to the need to look beyond physical building characteristics to increase energy efficiency, this work explores if specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In addition to the fact that for any survey analysis, such fundamental insight is necessary, and there are studies reporting direct interdependencies between demographics and energy-building interactions. For instance, the following patterns are reported: correlations between gender and thermal comfort (Sintov et al, 2019); gender and age correlations with thermal comfort preference and reactions to indoor environment changes (Schweiker et al, 2018); demographics and willingness association with DR strategies (Nilsson et al, 2018); family age structure associations with home energy consumption patterns and adoption of new energy-related technologies (Mills and Schleich, 2012); associations and disparities between spatial, racial/ethnic and EUI (Reames, 2016); ethnicity and financial burden of home energy expenses (Drehobl and Ross, 2016); ethnicity and home energy efficiency (Bednar et al, 2017); and demographic factors and willingness to accept an energy audit (Hewitt and Wang, 2020). Table 1 shows a summary of these studies, presenting the interacting factors and related findings.…”
Section: Methodology and Survey Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the fact that for any survey analysis, such fundamental insight is necessary, and there are studies reporting direct interdependencies between demographics and energy-building interactions. For instance, the following patterns are reported: correlations between gender and thermal comfort (Sintov et al, 2019); gender and age correlations with thermal comfort preference and reactions to indoor environment changes (Schweiker et al, 2018); demographics and willingness association with DR strategies (Nilsson et al, 2018); family age structure associations with home energy consumption patterns and adoption of new energy-related technologies (Mills and Schleich, 2012); associations and disparities between spatial, racial/ethnic and EUI (Reames, 2016); ethnicity and financial burden of home energy expenses (Drehobl and Ross, 2016); ethnicity and home energy efficiency (Bednar et al, 2017); and demographic factors and willingness to accept an energy audit (Hewitt and Wang, 2020). Table 1 shows a summary of these studies, presenting the interacting factors and related findings.…”
Section: Methodology and Survey Structurementioning
confidence: 99%
“…Therefore, it is necessary to design a precise approach to enable a comparison. In addition, Hewitt et al directly linked the social variables of humans to a specific energy efficiency practice in a building (Hewitt and Wang, 2020). They demonstrated that 'the chances of taking an energy audit decrease by 43% if the occupant is a tenant,' quantifying a human social pattern by considering a building efficiency aspect.…”
mentioning
confidence: 99%
“…Hewitt and Wang [17] analysed the Residential Energy Consumption Survey (USA) data from 2015. A binary logistic regression was applied to determine if selected socioeconomic and demographic factors influence the decision to undertake an energy audit.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To enhance support of the decision-making process of modernisation, various methods and tools were developed [19][20][21]. Representative buildings [22] or correlation-based models were also used [12,17,23].…”
Section: Literature Reviewmentioning
confidence: 99%